Studi Kasus Bullying Dan Penanganannya Pada Kelas Bawah Di SD Muhammadiyah 5 Surakarta - Putro, Lingga Margiyanto, Drs. Saring Marsudi, SH. M.Pd (2016)
ABSTRACT Lingga Margiyanto Putro/A510120043. THE CASE STUDY ON BULLYING AND HANDLING ON THE LOWER GRADE IN PRIMARY SCHOOL 5 MUHAMMADIYAH OF SURAKARTA. Essay. The Faculty of Education, Muhammadiyah University of Surakarta. April, 2016. This study aimed to know: 1) The classroom action by teachers of lower classes in SD Muhammadiyah 5 Surakarta against bullying, 2) The forms of bullying that occurs in the lower classes in SD Muhammadiyah 5 Surakarta, 3) Countermeasures are carried out by teachers against bullying the lower classes in SD Muhammadiyah 5 Surakarta, 4) The problem faced by teachers in handling cases of bullying at the lower classes at SD Muhammadiyah 5 Surakarta. This research is descriptive qualitative research with case study design (case studies). The informants are the headmaster, first grade teacher, second grade teacher, third grade teacher, first grade students, second grade students, and third grade students. Techniques of collecting data, namely observation, interview, documentation, and field notes. Techniques for analyzing data are display of data, reduction of the data, and conclusion. Data validity used triangulation techniques and triangulation of sources. The results of this research is to show the problem solving by the teachers in SD Muhammadiyah 5 Surakarta which is the forms of bullying made by the students. Problem solving by the teachers of lower classes include: 1) Call the students involved in bullying, 2) Investigate the real problems occur, 3) Give advices to students related with content of the learning, 4) Grow the soul of empathy, 5) Implant the religious values, 6) Have students record book case, 7) Confronted with the headmaster and if necessary to call; their parents if bullying cases difficult to handle. Forms of bullying made by students are divided into three forms, namely: physical bullying, verbal bullying and psychological or relational bullying. Forms of physical bullying such as hitting, pushing, kicking. Forms of verbal bullying such as mock and call the other students as a parent's name. Form of psychological or relational bullying is excommunication of the other students. This result of the study concluded that the teachers of lower classes has done solve the problem of bullying made by lower classes at SD 5 Muhammadiyah Surakarta. Keywords: bullying, problem solving, lower class.